Fra det lærde konvent : Seks breve om præster og præsteuddannelse - Lindhardt (†), P. G. (Kirkehistoriske Samlinger, 1988)
These six letters introduce a life-long correspondence between two members of »The Learned Convention«, Pastor Hans Koch (1867-1949) and Professor Valdemar Ammundsen (1875-1936). The first four letters are on the subject of the well-known contest for the Chair of Ecclesiastical History in 1901 (Kirkehistoriske Samlinger 1970, pp. 85-116), in which Koch puts forward arguments to Ammundsen in favour of J. Oskar Andersen (1866-1959) as the best suited for the job. After the appointment of Ammundsen to the professorship, however, Ammundsen confirms his friendship with Koch, and in the last two letters they discuss a suggestion in 1906 concerning the founding of a theological college in addition to, or in replacement of the University degree course in theology.